Measuring Perceptions of Appropriate Prison Sentences in the United States, 2000 - Cohen, Mark A. ([Verlag nicht ermittelbar], 2004)
This study examined the public's preferences regarding sentencing and parole of criminal offenders. It also investigated the public's willingness to pay for particular crime prevention and control strategies and tested new methods for gathering this kind of information from the public. This involved asking the public to respond to a series of crime vignettes that involved constrained choice. The study consisted of a telephone survey of 1,300 adult respondents conducted in 2000 in the United States. Following a review by a panel of experts and extensive pretesting, the final instrument was programmed for computer-assisted telephone interviews (CATI). The questionnaire specifically focused on: (1) the attitudes of the public on issues such as the number of police on the street, civil rights of minority groups, and the legal rights of people accused of serious crimes, (2) the randomized evaluation of preferred sentencing alternatives for eight different crime scenarios, (3) making parole decisions in a constrained choice setting by assuming that there is only enough space for one of two offenders, (4) the underlying factors that motivate the public's parole decisions, and (5) respondents' willingness to pay for various crime prevention strategies.